Application Analysis of Criminal Sanctions for Embezzlement of Tax Fees Deposits for Land and Building Rights (BPHTB) Acquisition Committed by Notaries - PPAT - Abdilla, Enrian Yaurin (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
In practice, Notary or PPAT often act as intermediaries for depositing the Acquisition of Rights over Land and Buildings Tax BPHTB payments to facilitate the transaction process. However, it is regrettable that some individuals serving as Notaries occasionally abuse their power and authority regarding BPHTB payments. The type of research conducted in this paper is Doctrinal. The results of the discussion indicate that the responsibility of a Notary should be to carry out their duties and authority properly and firmly, without violating the rules governing their position. The conclusion drawn from this analysis is that a Notary is responsible for the assistance provided in the BPHTB payment process for clients, and not for exploiting the money for personal interests. Such actions can cause losses to clients and the state. The legal consequences for Notaries who abuse their authority include criminal sanctions and the obligation to compensate clients who suffer losses due to their actions.